"Shh!" bleaching as representation of the silencing of women - de Leon, Kristelle Benice T.
This thesis acknowledges the existence of the long history of how patriarchy has long muffled women's voices that perpetuates their subordination. Culture of the silence amongst women is so accepted that many don't know that this culture even exists. Through studio research, the reductive and erasing properties of bleaching agents is used by bleaching printed images of women in fabric to metaphorically represent and articulate the existence of silencing imposed to women brought about by the colonization that is strengthen and still prevalent in Philippine culture. The work is viewed through the lens of feminist critical theory in which this study investigates the ways that patriarchy has been systemized. It has instilled that women's gender is subordinate than men and that women should be meek and submissive to them. This work also mediates some of the societal constraints set on women's speech and visibility because of the constructed ideal images of women that has been perpetuated by the male discourse.